Rationale and study design for the Social Environment and Cognitive Health in Urban and Rural Areas Study - Adam R Roth; Siyun Peng; Jafnun Nudrat Jarin; Tianyao Qu; Maleah Fekete; Brea L Perry (The Journals of Gerontology, Series B: Psychological Sciences and Social Sciences, 2026)
Abstract Objective The Social Environment and Cognitive Health in Urban and Rural Areas study was designed to examine cognitive health disparities in later life. It gathers data on access to social resources, engagement in cognitively stimulating interactions, and exposure to activity spaces. Methods We enrolled 510 participants from 41 Indiana counties during baseline data collection in Fall 2023. All participants completed a computer-assisted personal interview survey that collected data on their cognitive, mental, and physical health, personal networks, sociodemographic attributes, occupational history, lifestyle activities, and social support. Two hundred and seventy-three participants completed a follow-up module in which they used a smartphone to record ecological momentary assessments (EMAs) that were administered four times per day for seven days. Results The mean age was 69.9 years. Most participants were women (64.5%), White (90.2%), and retired (54.5%). The average participant named 5.38 network members. Participants were at home (70.7%) and alone (60.2%) for the majority of their EMAs. Approximately one third of the sample scored below a recommended cutoff for mild cognitive impairment on the Montreal Cognitive Assessment. Discussion We conclude by outlining a research agenda that (1) characterizes the social networks, interactions, and place-based activities of participants across geographic contexts, and (2) assesses the potential pathways between a combination of networks, interactions, and activities and cognitive function.